Superpowers and regional powers' soft power in Kazakhstan - Yessirkep, Saken; Abdrakhmanova, Gaukhar S.; Zhumashov, Yerkebulan; Pussyrmanov, Nurbek (Frontiers in Political Science, 2025)
Since gaining its independence in 1991, Kazakhstan has sought to balance its foreign policy toward those of the superpowers and regional powers. This study conducts a literature review and analyses the soft power strategies of superpowers and regional powers toward Kazakhstan, and the country's endeavors to avoid being dominated by a single country to maintain a balanced relationship with all the great powers. The data is collected through qualitative interviews with Kazakhstan officials who have lower- and middle-level executive experience in security organizations. Overall, pragmatic relations with all foreign actors are deeply engrained in the mindset of Kazakhstan's middle-management officials, which indicates the development of balanced reports for higher decision-makers, leading to balanced relations with other powers.